Skills Of Clinical Supervision For Nurses : a Practical Guide for Supervisees, Clinical Supervisors and Managers. - Bond, Meg (McGraw-Hill International (UK) Ltd., 2011)
This book aims to provide a practical and accessible, skills-based text on how to implement and engage in clinical supervision. Written in an accesible style, this book provides comprehensive coverage of the nursing world, with a practical focus, clear framework and exercises to guide learning.